## marcybaby 2 years ago Find the general term an for the geometric sequence a1=-3 and a2=6?

1. marcybaby

$a_{1}=-3 and a_{2}=6$

use the formula : an = a1 r^(n-1) with a1 is given -3 and to get the ratio(r), defined r = a2/a1 = 6/-3 = -2 therefore, an = a1 * r^(n-1) an = -3 * (-2)^(n-1) |dw:1367598379663:dw|

3. marcybaby

4. nincompoop

it is not the answer, rather hint as how to solve the problem.

5. marcybaby

ahhh!! i'm so lost and confused!! @nincompoop

6. waterineyes

Can you find here the common ratio "r" ??

7. marcybaby

-2?

8. waterineyes

Yep..

9. waterineyes

So, general term can be found as: $\large \color{green}{a_n = a \cdot r^{n-1}}$

10. waterineyes

a = -3 and r = -2.. Plug in and find..

11. marcybaby

6?

12. waterineyes

How?

13. waterineyes

Use that formula,

14. marcybaby

-3(-2)^n-1?

15. waterineyes

Yep, this is the general term you require...

16. marcybaby

okay, but I am stuck here. I dont what is the next step

17. marcybaby

i get 6^n-1?

18. waterineyes

Hey, this is the required answer, you can't solve it further..

19. marcybaby

so this cant get be simplified any more?

20. waterineyes

No..

21. waterineyes

$\large a_n = -3\cdot (-2)^{n-1}$

22. marcybaby

okay... how come tho? 6^n-1 looks like an ideal answer to me.

23. waterineyes

You cannot multiply $$-3$$ with $$(-2)^{n-1}$$

24. marcybaby

ohhhhhhhhhhh!!!!!!!!!! duh!! now i get it! my brain hurts been studing all week.

25. waterineyes

It is okay..

26. marcybaby

thank you for your time and patience

27. waterineyes

You are welcome dear..